Amphibiomorphic modeled and painted pottery from argentine patagonia and Central-Southern Chile. Functional interpretation and identification of species based on mimetic and aposematic traits - Perez, Alberto Enrique (2018)
This work aims to identify attributes or features related to endemic amphibians in modeled and painted pottery from central-southern Chile and north-western Argentina. From this work, we were able to identify four species of amphibians represented in certain types of modeled and painted pottery, and we also complemented this data with modern references and ethnohistorical chronicles of the potential use given to this pottery in particular. This contribution postulates that some elements of the black-onred pottery of the Early Ceramic Period of Araucaniá in central-southern Chile and of Patagonia in northwestern Argentina, seek to highlight amphibiomorphic characteristics such as exophthalmia (protruding eyes) and aposematism (brilliant coloring and brightness of the vessel by using an engobe decoration). Based on the ethnohistorical data of the area, it is also proposed that these vessels could be linked to the exclusive use of highly toxic substances. Finally, the results allowed us to explore the close ecological interaction between human groups and woodlands.